Nanoscale conductive pattern of the homoepitaxial AlGaN/GaN transistor. (26th February 2015) - Pérez-Tomás, A; Catalàn, G; Fontserè, A; Iglesias, V; Chen, H; Gammon, P M; Jennings, M R; Thomas, M; Fisher, C A; Sharma, Y K; Placidi, M; Chmielowska, M; et al.
Abstract: The gallium nitride (GaN)-based buffer/barrier mode of growth and morphology, the transistor electrical response (25–310 °C) and the nanoscale pattern of a homoepitaxial AlGaN/GaN high electron mobility transistor (HEMT) have been investigated at the micro and nanoscale. The low channel sheet resistance and the enhanced heat dissipation allow a highly conductive HEMT transistor ( I ds  > 1 A mm −1 ) to be defined (0.5 A mm −1 at 300 °C). The vertical breakdown voltage has been determined to be ∼850 V with the vertical drain-bulk (or gate-bulk) current following the hopping mechanism, with an activation energy of 350 meV. The conductive atomic force microscopy nanoscale current pattern does not unequivocally follow the molecular beam epitaxy AlGaN/GaN morphology but it suggests that the FS-GaN substrate presents a series of preferential conductive spots (conductive patches). Both the estimated patches density and the apparent random distribution appear to correlate with the edge-pit dislocations observed via cathodoluminescence. The sub-surface edge-pit dislocations originating in the FS-GaN substrate result in barrier height inhomogeneity within the HEMT Schottky gate producing a subthreshold current.